Triboelectric nanogenerators for enhanced degradation of antibiotics via external electric field. (March 2022) - Mo, Jilong; Liu, Yanhua; Fu, Qiu; Cai, Chenchen; Lu, Yanxu; Wu, Wanhai; Zhao, Zhenxia; Song, Hainong; Wang, Shuangfei; Nie, Shuangxi
Abstract: Using clean and random energy to solve the problem of antibiotic water pollution is an effective way to achieve sustainable development of the energy and environment. Wave energy in the aeration tank of aerobic biological technology is often ignored, resulting in serious energy waste. Metal-organic frameworks have been widely explored in the fields of energy utilization and environmental remediation. However, the photocatalytic efficiency is limited by the recombination of electrons and holes. In this work, a crowned triboelectric nanogenerator (C-TENG) was developed to enhance photocatalytic efficiency for degrading antibiotics. C-TENG converts wave energy in the aeration tank into electricity. An external electric field could be generated between two electrodes, which can promote the effective separation of photogenerated electrons and holes. Driven by the water wave with the acceleration of 5 m/s 2, the removal efficiency of tetracycline could reach 95.89% within 80 min. The presence of the external electric field could generate more superoxide radicals (·O2 - ), hydroxyl radicals (·OH) and holes (h + ), which plays an important role in improving photocatalytic efficiency. This work proposes an efficient, environmentally friendly and low-cost antibiotic degradation method, providing an effective way to purify the water. Graphical Abstract: ga1 Highlights: A self-powered photocatalytic degradation system is proposed. The self-powered photocatalytic system has a high photocatalytic efficiency. External electric field plays a significant role in the photocatalytic reaction. A coronal triboelectric nanogenerators convert wave energy in the aeration tank into electricity.